The Routledge handbook of the sociopolitical context of language learning
1 online resource.
Keywords: "The Routledge Handbook of the Sociopolitical Context of Language Learning is a compelling examination of how language education must adapt to our rapidly changing world. This book explores the need for a fresh perspective on language learning, moving beyond traditional methods to address the complexities of today's global landscape. It delves into the impact of geopolitical shifts, cultural exchanges, and social justice issues on language education. The book offers a blend of theoretical insights and practical approaches, highlighting how language learning intersects with global politics and cultural diversity. It examines case studies from various countries, including Ukraine and Oman, to reveal how language policies and practices are evolving in response to contemporary challenges. By integrating themes of identity, equity, and intercultural understanding, the book presents groundbreaking content that pushes for more inclusive and effective language education. Ideal for educators, policymakers, and anyone interested in the future of language learning, this book provides valuable perspectives on how to rethink and redesign language education to better serve a diverse and interconnected world. It offers practical strategies and thought-provoking analyses, making it an essential resource for navigating the complexities of modern language teaching and learning"--